BASE MOVEMENT INFLUENCE OF HITTING BALL USING HAD AND FOOT IN FOOTBALL GAME - Midhat Mekić; Rašid Hadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
We had analyzed movements abilities influence on situation movement abilities applied on evaluation of strenght of hitting ball using foot and had football game, played by 13 years old boys. In aim of that we had choose 24 movement facts and 3 situations tests of football game. In those examples we had got rezults which are proof that these about influence of movement element s on rezults in analiyzed test.